HUBUNGAN MODEL PEMBELAJARAN TUNTAS DAN METODE DISCOVERY TERHADAP MOTIVASI BELAJAR SISWA DI SMA NEGERI 1 KUPANG - Benu, Asti Yunita (Universitas Islam Negeri Alauddin Makassar, 2020)
The relationship of mastery learning models and methods of discovery due to the motivation to learn of students. Each student has a different motivation to learn inborn but is not ready to be a motivation to learn. One container to form a motivation to learn that is through education, namely concrete form through the learning process. But the learning process in the classroom is still dominated by the role of the teacher (teacher centered) and less precise methods used by teachers in teaching. More teachers putting students as objects and not as subjects students. This study aims to: (1) Knowing the relationship mastery learning model due to the formation of the motivation to learn of students at SMAN 1 Kupang, (2) Knowing the relationship discovery method to motivation to learn formation of students at SMAN 1 Kupang, (3) determine the relationship of mastery learning thoroughly and use methods discovery on motivation to learn formation of students at SMAN 1 Kupang. This research is a quantitative correlation using the questionnaire method. Mechanical testing data in this study is a reliability test questionnaire, questionnaire validity, normality test, homogeneity test and t-test statistics. The results of the analysis obtained after correlated, the first correlation between X1 on Y, t = 2.819 t table while the error level of 0,05) = 1.721.a5% ( 0,05) = 1.721. The second correlation between X2 on Y, t = 4.211 t table while the error level of 5% ( 0.05). The third correlation multiple correlation between X1, X2 on Y obtained by R of 0.67, F 12.77,p = 0.000 > 0,05. Based on these calculations it can be concluded that (1) there is a positive and significant relationship between the variables of mastery learning models due to the motivation to learn of the student, (2) there is a positive and significant relationship between the variable method of discovery to the motivation to learn of students, and (3) there is a positive and significant relationship between the variables mastery learning models and methods of discovery due to the motivation to learn of students.